„Die Moskauer Sonne scheint überall“. Die sowjetische Hauptstadt als Raum der Utopie in Das neue Moskau (1938) und Die Schweinepflegerin und der Hirt (1941) - Chertenko, Alexander (Studia Rossica Posnaniensia, 2021)
Basing on Aleksandr Medvedkin’s New Moscow and Ivan Pyryev’s The Swineherd and the Shepherd, this case study analyses the way the “new” Moscow was represented as a space of realised utopia in the Soviet socialist realist films of the 1930s and at the beginning of the 1940s. Functioning as a supranational centre of the Soviet “affirmative action empire” (Terry Martin), the cinematographic Moscow casts off all constraints of ‘Russianness’ in order to become a pan-Soviet model which, both in its architecture and semantics, could epitomize the perfect city and the perfect state. The comparative analysis of both films demonstrates that, although both directors show Moscow through the lens of the so-called “spaces of celebration” (Mikhail Ryklin), ‘their’ Soviet capital does not compensate for the “traumas of the early phases of enforced urbanization”, as Ryklin supposed. Rather, it operates as a transformation machine whose impact pertains only to periphery and can be effective once the representatives of this periphery have left Moscow. The complex inclusion and exclusion mechanisms resulting from this logic turn the idealised Soviet capital into a space which only the guests from peripheral regions can perceive as utopian. The ensuing suppression of the inner perspectives on ‘utopian’ Moscow is interpreted here as a manifestation of the “cinematic unconscious”, which accounts for the anxieties of the inhabitants of the capital concerning both Stalinist terror and their own hegemony in a society haunted by the purges.